2015
DOI: 10.1002/2014jb011524
|View full text |Cite
|
Sign up to set email alerts
|

The 11 March 2011 Tohoku tsunami wavefront mapping across offshore Southern California

Abstract: The 11 March 2011 (M w = 9.0) Tohoku tsunami was recorded by a temporary array of seafloor pressure gauges deployed off the coast of Southern California, demonstrating how dense array data can illustrate and empirically validate predictions of linear tsunami wave propagation characteristics. A noise cross-correlation method was used to first correct for the pressure gauge instrument phase response. Phase and group travel times were then measured for the first arrival in the pressure gauge tsunami waveforms fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Therefore, only 27 tsunami waveforms at DART and APG stations are used for waveform inversion (Figure b). Because the DPG waveforms are accurate in terms of the tsunami arrival times and wave periods [ Sheehan et al , ; Lin et al , ], we correct the observed amplitudes of 30 DPG records based on tsunami simulations from the source model. This correction makes it possible to use DPG data together with the DART and APG data to fulfill the requirement on the data's spatial coverage for the tsunami data assimilation method.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, only 27 tsunami waveforms at DART and APG stations are used for waveform inversion (Figure b). Because the DPG waveforms are accurate in terms of the tsunami arrival times and wave periods [ Sheehan et al , ; Lin et al , ], we correct the observed amplitudes of 30 DPG records based on tsunami simulations from the source model. This correction makes it possible to use DPG data together with the DART and APG data to fulfill the requirement on the data's spatial coverage for the tsunami data assimilation method.…”
Section: Methodsmentioning
confidence: 99%
“…These arrays enable us to observe tsunamis propagating across such an array directly. Tsunami recordings by using an OBPG array have been analyzed by various approaches: for example, to estimate tsunami source processes (e.g., Fukao et al., 2018; Hossen et al., 2015; Kubota, Kubo, et al., 2021), to reconstruct tsunami wavefields by data assimilation (e.g., Gusman et al., 2016; Wang & Satake, 2021), to detect scatterers of tsunami waves by the beamforming method (Kohler et al., 2020), and to derive a phase velocity map of tsunamis by the eikonal tomography (Lin et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…S2C), which depends on the frequency and water depth of the reference station (20,21). The frequency-dependent travel time (22)(23)(24) and propagation direction at the reference station are sensitive to the tsunami source location (Fig. 2; see also fig.…”
Section: Resultsmentioning
confidence: 99%